2014
DOI: 10.1002/rmv.1782
|View full text |Cite
|
Sign up to set email alerts
|

Neurological aspects of human parvovirus B19 infection: a systematic review

Abstract: Parvovirus B19 has been linked with various clinical syndromes including neurological manifestations. However, its role in the latter remains not completely understood. Although the last 10 years witnessed a surge of case reports on B19-associated neurological aspects, the literature data remains scattered and heterogeneous, and epidemiological information on the incidence of B19-associated neurological aspects cannot be accurately extrapolated. The aim of this review is to identify the characteristics of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
65
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 102 publications
3
65
0
3
Order By: Relevance
“…13 Little has been published on the treatment of acute parvovirus B19 infection, probably because when the infection does cause symptoms, these tend to be self-limiting. 34 In our series, clinical improvement occurred rapidly in patients treated with systemic corticosteroids. 13,31 Long-term administration of systemic corticosteroids has been associated with an increased risk of infections.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…13 Little has been published on the treatment of acute parvovirus B19 infection, probably because when the infection does cause symptoms, these tend to be self-limiting. 34 In our series, clinical improvement occurred rapidly in patients treated with systemic corticosteroids. 13,31 Long-term administration of systemic corticosteroids has been associated with an increased risk of infections.…”
Section: Discussionsupporting
confidence: 48%
“…Possible signs of persistent infection were present in immunodepressed patients, coinciding with observations in the majority of reports published. 33 However, in a systematic review of parvovirus B19 infection associated with neurological manifestations, Barah et al 34 reported that a combined regimen of systemic corticosteroids and immunoglobulin infusion therapy was effective. A number of articles have described the successful use of immunoglobulin infusion therapy in the treatment of persistent infection.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, 52% patients presented manifestations other than joint or cutaneous features (i.e., renal, neurological, muscular, hepatic, pleuro-pericardial or splenic involvement), which highlights the need to seek these complications in patients with HPV-B19 infection. Of note, the present study adds a fifth case of Guillain-Barré syndrome related to HPV-B19 infection (patient 22) [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Los corticoides sistémicos se relacionan, cuando son administrados durante largos periodos, con un aumento de la predisposición a padecer infecciones 33 . Sin embargo, en la revisión de Barah et al de los casos descritos en la literatura de infección por parvovirus B19 asociada a afectación neurológica, los corticoides sistémicos asociados a infusión de inmunoglobulinas aparecen como un tratamiento eficaz 34 . En nuestro estudio los pacientes que recibieron corticoterapia sistémica mejoraron clínicamente en un corto periodo de tiempo.…”
Section: Discussionunclassified